Coping with the extremes: comparative osteology of the tepui-associated toad Oreophrynella and its bearing on the evolution of osteological novelties in the genus. Issue 1 (3rd March 2020) - Kok, Philippe J R; van der Velden, Milan A J; Means, D Bruce; Ratz, Sebastian; Josipovic, Iván; Boone, Matthieu; McDiarmid, Roy W
Abstract: The only study of the osteology of the toad genus Oreophrynella dates back to 1971 and was based on a single species. Here, we use high-resolution X-ray microcomputed tomography to analyse the osteology of all nine described Oreophrynella species, which are compared with representatives of other bufonid lineages. Oreophrynella is unique among bufonids in having opposable digits. Osteological synapomorphies confirmed for the genus are as follows: presence of parietal fontanelles and exposed frontoparietal fontanelle, absence of quadratojugal, five presacral vertebrae, distally enlarged terminal phalanges and urostyle greatly expanded into flanges. Ancestral character reconstruction indicates that arboreal habits in some Oreophrynella species are likely to have evolved after the evolution of opposable digits. Opposable digits, in combination with an extension of the interdigital integument and the relative length/orientation of the digits, are likely to be adaptations to facilitate life on rocky tepui summits and an exaptation to arboreality. Cranial simplification in Oreophrynella, in the form of cranial fontanelles and absence of the quadratojugal, is possibly driven by a reduction of developmental costs, increase in flexibility and reduction of body weight. Cranial simplification combined with the shortening of the vertebral column and the shift towards a partly firmisternal girdle might be adaptations to the peculiar tumbling behaviour displayed by Oreophrynella .